2006
DOI: 10.1002/ppul.20406
|View full text |Cite
|
Sign up to set email alerts
|

IPPB-assisted coughing in neuromuscular disorders

Abstract: In neuromuscular disorders, reduced peak cough flows (PCFs) are considered to increase the risk of respiratory complications such as pneumonia or chronic atelectasis. Different methods were described to improve PCF. However, these studies were primarily carried out in adults, and there is limited information regarding the use and efficacy of these methods in children with respiratory muscle weakness. The aim of this study was to investigate whether hyperinsufflation with an intermittent positive-pressure breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 25 publications
0
49
0
7
Order By: Relevance
“…The usefulness of assisted coughing by intermittent positive pressure breathing to enhance peak cough flow could be shown in a recent investigation. 17 In 12 of 15 patients of our study population assisted coughing was also helpful to overcome acute chest infection. Only three patients prolonged ventilation time.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The usefulness of assisted coughing by intermittent positive pressure breathing to enhance peak cough flow could be shown in a recent investigation. 17 In 12 of 15 patients of our study population assisted coughing was also helpful to overcome acute chest infection. Only three patients prolonged ventilation time.…”
Section: Discussionmentioning
confidence: 90%
“…Assisted coughing techniques such as glossopharyngeal breathing, the in-/exsufflator or IPPB (Intermittent Positive Pressure Breathing) assisted coughing demonstrated positive effects on peak cough flows in neuromuscular patients. [11][12][13][14][15][16][17] Additional treatment such as early antibiotic treatment or influenza and pneumococcal vaccination may help to prevent severe respiratory complications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the broad range reported in the literature, the improvements seen in this present study align with the change from unassisted cough peak flow to air stacking-assisted cough peak flow values of ϩ35% to ϩ71% that other authors report. 11,13,14,26 A recent study reported that air stacking can be learned by children with severe muscle weakness. 27 In 18 subjects affected by spinal muscular atrophy and congenital muscular dystrophy, air stacking was shown to be an effective airway clearance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…When hyperinflated in this manner to maximum insufflation capacity, subsequent cough maneuvers are performed with increased inspiratory volume. Air is passively delivered using a positive pressure device, such as a ventilator or resuscitator bag, 11 or via glossopharyngeal breathing. 12 When using glossopharyngeal breathing or a ventilator, patients need to coordinate both opening of their glottis during each insufflation and closure at the end in order to hold the stacked air and increase inspiratory capacity.…”
Section: What Is Air Stacking?mentioning
confidence: 99%
“…As consequências diretas desse acometimento são a diminuição da pressão gerada durante a tosse levando a episódios de broncoaspiração e retenção de secreções em vias aéreas 8,15 . Sabe-se que o treino de força no músculo reto abdominal através de dispositivos de expiração forçada, melhora o recrutamento de fibras, e consequentemente a tosse, mas existe uma série de condições clínicas e limitações que contraindica o uso destes para essa finalidade [16][17][18][19] . Além disso, já existem evidências que a eletroestimulação transcutânea em musculatura respiratória tem bons efeitos em pacientes crônicos, inclusive neurológicos, em quadros de atrofia muscular [20][21][22][23][24][25] .…”
unclassified